Institutions versus Geography : Subnational Evidence from the United States - Romero-Barrutieta, Alma (IMF Working Papers; Working Paper ;, 2006)
Empirical studies of the impact of geography and institutions on growth and development at the international level have become common place, but the high degree of abstraction at that level has led to calls for subnational studies. This paper examines these issues for a region of the United States, Appalachia, where the specific factors at play are identified and measured thus obviating the need for instrumental variable techniques. The evidence suggests that initial conditions, including both geography and institutions, are very important for economic development, having significant effects lasting hundreds of years.